2021
DOI: 10.1016/j.jsams.2021.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Exertional heat fatalities in Australian sport and recreation

Abstract: Objectives: To describe the number and case characteristics of sport and recreation-related exertional heat deaths in Australia and summarise recommendations derived from case narratives. Design: Descriptive, population-based, retrospective cohort study. Methods: Cases were identified using the National Coronial Information System (NCIS) through multiple search strategies comprising queries, keywords and cause of death codes. Cases were included where there was evidence that the deceased was actively engaged i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Various heat-safety resources for sport and leisure organisations across Australia focus on generic prevention strategies, but do not always assess risk factors and provide guidelines for treatment. Fortington 12 Exertional heat fatalities in Australian sport and recreation A retrospective analysis of exertional heat deaths in Australia revealed that exertional heat deaths were far more prevalent in outdoor recreation than in organised sport. The largest proportion of deaths occurred in hiking.…”
Section: Sports Policy and Heat Stress Protectionmentioning
confidence: 99%
“…Various heat-safety resources for sport and leisure organisations across Australia focus on generic prevention strategies, but do not always assess risk factors and provide guidelines for treatment. Fortington 12 Exertional heat fatalities in Australian sport and recreation A retrospective analysis of exertional heat deaths in Australia revealed that exertional heat deaths were far more prevalent in outdoor recreation than in organised sport. The largest proportion of deaths occurred in hiking.…”
Section: Sports Policy and Heat Stress Protectionmentioning
confidence: 99%